Novel fractional order sinusoidal oscillators using operational trans resistance amplifier - Battula Tirumala Krishna; Vanitha Kakollu; Manchala Madhusudhan Prasad (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2025)
The design of fractional order circuits in very large-scale integration (VLSI) domain is gaining the interest of many researchers. At the same time design of fractional circuits using the current mode devices is attracting the research community. In this paper, several possible fractional order sinusoidal oscillators using operational trans resistance amplifier (OTRA) as a basic building block is presented. The necessary condition for the frequency of oscillation and condi tion for oscillations is derived. Fractional order operator sα is the most crucial one to be approximated. In this paper, the fractional order element is approxi mated by the continued fraction expansion (CFE). The approximation is carried out up to fifth order. The circuits are tested with the simulation software named LTspice. The results agree with the theoretical one. The proposed circuits of fers a frequency of 15 MHz, 20 MHz, and 25 MHz which is higher in value as compared to the existing circuits. The proposed circuits finds applications in bio medical, communication circuits.